Aperiodically intermittent control for synchronization of stochastic coupled networks with semi-Markovian jump and time delays. (November 2020) - Guo, Beibei; Shi, Peng; Zhang, Chiping
Abstract: In this paper, the problem of exponential synchronization is studied for a class of stochastic coupled networks with semi-Markovian jump and multiple time delays. A nonlinear aperiodical intermittent control is designed to synchronize the underlying networks. By Lyapunov approach and graph theory, some new synchronization criteria are derived, which are closely related to the maximum uncontrolled ratio of intermittent control and the network topology structure. Synchronization analysis for coupled oscillators is conducted to show the practical potential of the obtained theoretic results. Also, two numerical examples are given to illustrate the effectiveness of control strategy.